Knowledge and Influence of Predatory Journals in Dermatology: A Pan-Austrian Survey - Georg Richtig; Markus Richtig; Wolfram Hoetzenecker; Werner Saxinger; Bernhard Lange-Asschenfeldt; Andreas Steiner; Robert Strohal; Christian Posch; Johann W. Bauer; Robert R. Müllegger; Teresa Deinlein; Norbert Sepp; et al. (Medical Journals Sweden, 2018)
The aim of this study was to assess the knowledge and influence of predatory journals in the field of dermatology in Austria. A total of 286 physicians (50.5% men) completed a questionnaire. The vast majority of subjects read scientific articles (n = 281, 98.3%) and took them into consideration in their clinical decision-making (n = 271, 98.5% of participants that regularly read scientific literature). Open access was known by 161 (56.3%), predatory journals by 84 (29.4%), and the Beall's list by 19 physicians (6.7%). A total of 117 participants (40.9%) had been challenged by patients with results from the scientific literature, including 9 predatory papers. Participants who knew of predatory journals had a higher level of education as well as scientific experience, and were more familiar with the open-access system (p <0.001). These results indicate that the majority of dermatologists are not familiar with predatory journals. This is particularly the case for physicians in training and in the early stages of their career.